Unraveling Dissipation-Related Features in Magnetic Imaging by Bimodal Magnetic Force Microscopy - Miriam Jaafar; Agustina Asenjo (Applied Sciences, 2021)
Magnetic Force Microscopy (MFM) is the principal characterization technique for the study of low-dimensional magnetic materials. Nonetheless, during years, the samples under study was limited to samples in the field of data storage, such as longitudinal hard disk, thin films, or patterned nanostructures. Nowadays, thanks to the advances and developments in the MFM modes and instrumentation, other fields are emerging like skyrmionic structures, 2D materials or biological samples. However, in these experiments artifacts in the magnetic images can have strong impact and need to be carefully verified for a correct interpretation of the results. For that reason, in this paper we will explore new ideas combining the multifrequency modes with the information obtained from the experimental dissipation of energy associated to tip-sample interactions.